Influence of symmetric and asymmetric alterations of maxillary canine gingival margin on the perception of smile esthetics among orthodontists, dentists, and laypersons - Shashank Katiyar; Sumit Gandhi; Javed Sodawala; G Anita; Shaheen Hamdani; Suyog Jain (Wolters Kluwer Medknow Publications, 2016)
Introduction: Esthetics is one of the major concerns among people seeking orthodontic treatment, and its perception varies from person to person. Our objective was to determine the differences in the perception of smile esthetics among orthodontists, general dentists, and laypersons with respect to alteration in the maxillary canine gingival margin in close-up smile analyses. Materials and Methods: Close-up photograph of an ideal Indian female smile was selected. The images were digitally altered to create symmetrical images with the gingival margin levels of maxillary canine matching the central incisors. Twelve alterations were created in the gingival margin of the canine with discrepancies of 1, 2, and 3 mm in relation to the most superior point on the labial gingival margin of patient's central incisor and divided under four groups. Finally, close-up images of the smile were assessed by orthodontist, general dentist, and layperson who indicated the level of attractiveness of each smile on a visual analogue score. The data collected were then statistically analyzed by one-way analysis of variance followed by Newman-Keul's range test. Results: Most evaluators considered all the three components, i.e., lips, teeth, and gingiva while assessing the smile's attractiveness. Statistically significant differences were observed between different evaluator groups when considering bilateral increase in crown height by 2 and 3 mm. The perceptions of asymmetries in the gingival margin levels of the maxillary canines were 1.0 mm for orthodontists and 2.0 mm for laypersons. Conclusion: The result of this study suggested that the orthodontists were more critical than dentist and layperson in evaluating smile esthetics.